Analisis Framing Media CNN Indonesia dan Inilah.com dalam Pemberitaan Menkeu Purbaya yang Tidak Melegalkan Thrifting - Komang Juliani; Rieka Yulita Widaswara; Ida Bagus Made Arjana (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study aims to analyze how CNNIndonesia.com and Inilah.com frame the controversy surrounding the government’s prohibition of thrifting led by Finance Minister Purbaya using Entman’s framing analysis model. The thrifting issue has gained public attention due to its connection with the legality of second-hand clothing imports, the livelihood of local traders, and the interests of the domestic textile industry. The study examines six news articles—three from CNN Indonesia and three from Inilah.com—through Entman’s four framing elements: problem definition, causal diagnosis, moral evaluation, and treatment recommendation. The findings reveal substantial differences between the two media outlets. CNN Indonesia tends to construct thrifting as a multilayered socio-economic issue, featuring diverse actors such as traders, legislators, and government officials, thus producing a more dialogical and contextual narrative. In contrast, Inilah.com emphasizes a firmer stance by highlighting the illegality of thrifting, the government’s strong enforcement actions, and the urgency of eradicating smuggling networks. These contrasting constructions reflect each outlet’s editorial orientation and targeted audience. The study underscores the importance of media literacy in helping the public critically interpret framing differences, particularly within economic and public-policy issues that significantly influence societal perception.